Importance to approve the stamp pro sports & recreation (2016)
In this paper grade is to conduct research on the general state of the importance of creating the stamp pro-sport aimed at children, adolescents and older adults as a population abandoned by the state in Colombia, is important for Colombia to establish a sense of social responsibility towards social rights, one of which is to encourage sports activity and promote them to start to protect special form when a population in a state of manifest weakness.